Prognostic value of serum lactate dehydrogenase and serum ferritin for abdominal neuroblastoma in children (Journal of Paediatric Surgeons of Bangladesh, 2024)
Backgrounds: For decades, age, MYCN status, stage, and histology have been used as neuroblastoma risk factors. Serum Lactate dehydrogenase (LDH) and ferritin are reproducible, easy to obtain, and prognostic, but they are never used in risk stratification. Purpose/Objective: The purpose of this study was to find out the prognostic value of serum LDH and ferritin in children with abdominal neuroblastoma. Materials/Methods: Nine children with abdominal neuroblastoma from 2020-2021 in four tertiary centers of Dhaka, who treated according to Socie’te’ Internationaled’OncologiePe’diatrique selected as study population and divided into low and high-risk groups. Age, sex, stage, histology, serum LDH, serum ferritin and events were analyzed using SPSS 22. Survival was calculated by Kaplan-Meier procedure Results: Sensitivity, specificity, positive predictive value and negative predictive value of serum LDH were 100%, 85.7%, 66.7% and 100% respectively in the prognosis of abdominal neuroblastoma in children at a cut-off point =1527.5. Sensitivity, specificity, positive predictive value, and negative predictive value of serum ferritin were 100%, 71.4%, 50% and 100% respectively in the prognosis of abdominal neuroblastoma in children at a cut-off point=581.There was no significant difference between the survival curves of both risk groups (p= 0.180) and between serum ferritin >581 and  £581 group (p= 0.089) according to log rank test. But there was significant difference between the survival curves of LDH >1527 and LDH  £1527.5 group according to log rank test (p= 0.027). Conclusion: Analysis of this study revealed that the risk of a worse event for children with abdominal neuroblastoma was greater and outcome was also worse for patients with serum LDH >1527.5 IU/L and serum ferritin >581 ng /ml. These markers can also be used for risk stratification in low to middle income countries. But further multi-centered study with longer period of follow up on larger sample size will be required to demonstrate the independent prognostic value of serum LDH and ferritin for abdominal neuroblastoma in children.Journal of Paediatric Surgeons of Bangladesh (2019) Vol. 10 (1 & 2): 43-48